Nellie Lou's hairdos - Sandford, John (New York : Warner Juvenile Books, 1989)
Nellie Lou, minding the hair shop in her mother's absence, works hard to create a satisfactory hairstyle for Miss Gump, who can never up her mind.
Keywords: Hairsytles-- Fiction; Hairdressing--Fiction